A Risk Management Framework for Large Scale Scrum using Metadata Outer Request Management Methodology - Adel, Rehab; Harb, Hany; Elshenawy, Ayman (International journal of advanced computer science & applications, 2022)
Recently, most software projects became naturally Distributed Agile Development (DAD) projects. The main benefits of DAD projects are cost-saving and being close to markets due to their distributed nature, such as in large-scale Scrum (LeSS). Developing LeSS projects leads to the emergence of challenges in risk management, especially the team collaboration challenges, where there is no standardized process for teams to communicate collaboratively. Team collaboration and the knowledge sharing is a vital resource for a large Scrum team's success. Hence, finding a dynamic technique that facilitates team collaboration in the LeSS environment is necessary. This paper proposes a risk management framework for LeSS using outer metadata requests. The proposed framework manages the outer requests amongst the distributed team. Therefore, it avoids missing team collaboration, risks, and threats to project completion. It also contributes to exchanging team skills and experience. The proposed framework is evaluated by applying it to two different case studies for large-scale Scrum projects. The evaluation results are given. The evaluation proved the effectiveness of the proposed framework.